Entrepreneurial Marketing Mindset as a Determining Factor for Digital Startup Success - Greian April Pangilinan; Sipah Audiah; Muhammad Rifat Shauqy; Otniel Feliks Putra Wahyudi (Pandawan Sejahtera Indonesia, 2025)
This research explores the Entrepreneurial Marketing Mindset as a critical determinant of digital startup success in Indonesia’s dynamic and competitive market environment. Startups often face significant challenges, including resource limitations, market uncertainty, and the pressing need for continuous innovation and adaptation to maintain relevance. This study employs a Quantita- tive Approach, gathering data from 100 digital startups that have been operating for over two years. Multiple Linear Regression Analysis was used to evaluate the relationship between Entrepreneurial Marketing Mindset and key success metrics, such as product innovation, adaptability to market demands, and customer satisfaction. The findings reveal that adopting an Entrepreneurial Marketing Mindset significantly enhances a startup’s ability to innovate and respond swiftly to changing market dynamics. By fostering flexibility and creativity, this mindset empowers startups to navigate uncertainties, overcome market fragmentation, and establish a competitive edge. These insights are not only relevant for Indonesia but also extend to other regions with similar market conditions. In Southeast Asia, for example, fragmented markets and cultural diversity demand customized approaches, while in South Asia, accelerating digital transformation calls for adaptability and innovative strategies. Startups that embrace this mindset can develop tailored marketing strategies, optimize resource utilization, and achieve sustainable growth. This research underscores the pivotal role of Entrepreneurial Marketing Mindset in building resilience, fostering innovation, and ensuring the long-term success of digital startups in highly dynamic environments.